Development of Collaborative Learning Model Based on Virtual Laboratory in Higher Education - Rudi Mulya; Diki Atmarizon (International Journal of Educational Dynamics, 2021)
In this study, collaborative learning based on a virtual laboratory was developed because the existing model did not integrate collaborative learning with a virtual laboratory. The research step begins with designing a virtual laboratory portal with Moodle software to provide practical management services. The trial was carried out by running an online collaborative practice by implementing the Breadboard Simulator and the TeamViewer application. The research subjects were 30 students of the DIII Electrical Engineering study program. The data collection instrument used a student perception questionnaire on student perceptions about instructional aspects. Descriptive analysis was carried out using the criteria for the level of perception. The results showed that the virtual laboratory-based collaborative learning model had a positive perception of the instructional aspect and increased student motivation in carrying out practical activities